Recentralization and vertical alignment in the French health‐care system. Issue 4 (16th January 2017) - Simonet, Daniel
Abstract: In foreign exemplars, key new public management (NPM) features such as decentralization and devolution of health‐care responsibilities had outcomes below expectations. Other NPM traits such as the patient as overseer of reforms or the empowerment of patient remained elusive. In France, the integration of public values such as greater participation of patients and local actors (NGOs and elected officials) and NPM‐driven private values such as performance evaluation has yet to be seen. Taking advantage of NPM's failings and austerity agenda, a French welfare elite regained control over health‐care policy decisions at the expense of regions and other local actors. NPM outcomes were below expectations. Austerity cures led to weakening of the regional decision spaces, which can be explained under the principal–agent relationship. Accountability shifted to managerial (the professionalization of hospital managers) and legal (governance via regulations) forms in a bid to restore central government control. A democratic recess results from the lack of public engagement in recent health reforms.